PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN DAN NILAI PASAR PERUSAHAAN PERBANKAN DENGAN METODE VALUE ADDED INTELLECTUAL COEFFICIENT - NOVIA WIJAYA (Jurnal Bisnis dan Akuntansi, 2012)
The purpose of this study is to investigate the influence of value creation efficiency, as measured by value added intellectual coefficients that consists of three components of a firms’ resource (capital employed, human capital, and structural capital) to financial performance: profitability and productivity, as measured by Return on Equity and Asset Turnover and to firms’ market value, as measured by Market to Book Value Ratio in Indonesian banking industry. This study objective is to give input for financial manager and investor in increasing financial performance and firms’ market value by investment in intellectual capital.Regression models were used to examine the influence of each component of the value creation efficiency on financial performance and firms’ market value. The data used in this study are taken from 26 Indonesia banks from the 2008-2011 public listing of banking companies. This empirical study uses purposive sampling technique and regression model for the data analysis.The research indicates that capital employed efficiency influences profitability, productivity and firms’ market value. The human capital efficiency and structural capital efficiency influence firms’ market value, but fails to influence profitability and productivity.